2012
DOI: 10.1002/hep.25773
|View full text |Cite
|
Sign up to set email alerts
|

Serine protease hepsin regulates hepatocyte size and hemodynamic retention of tumor cells by hepatocyte growth factor signaling in mice

Abstract: The liver architecture plays an important role in maintaining hemodynamic balance, but the mechanisms that underlie this role are not fully understood. Hepsin, a type II transmembrane serine protease, is predominantly expressed in the liver, but has no known physiological functions. Here, we report that hemodynamic balance in the liver is regulated through hepsin. Deletion of hepsin (hepsin 2/2 ) in mice resulted in enlarged hepatocytes and narrowed liver sinusoids. Using fluorescent microbeads and antihepsin … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

3
32
1

Year Published

2014
2014
2024
2024

Publication Types

Select...
5
3
1

Relationship

0
9

Authors

Journals

citations
Cited by 34 publications
(36 citation statements)
references
References 34 publications
(37 reference statements)
3
32
1
Order By: Relevance
“…Hepsin is not an essential gene and Hepsin knockout mice are viable and fertile [32, 33]; however, these animals exhibit hearing loss due to developmental deformities in the cochlea [34]. Moreover, Hepsin knockout mice display enlarged hepatocytes and narrowed liver sinusoids [35]. Consistent with the phenotype of Hepsin knockout mice, we did not observe any prominent deficiency in mice treated with Hepsin inhibitors; however, more careful examination will be necessary in the future.…”
Section: Discussionsupporting
confidence: 58%
“…Hepsin is not an essential gene and Hepsin knockout mice are viable and fertile [32, 33]; however, these animals exhibit hearing loss due to developmental deformities in the cochlea [34]. Moreover, Hepsin knockout mice display enlarged hepatocytes and narrowed liver sinusoids [35]. Consistent with the phenotype of Hepsin knockout mice, we did not observe any prominent deficiency in mice treated with Hepsin inhibitors; however, more careful examination will be necessary in the future.…”
Section: Discussionsupporting
confidence: 58%
“…1 The mass of the active protease domain fragment is 31 kDa and a further processing to a smaller 20-27 kDa form has been observed. 14,25 Three distinct hepsin fragments with expected sizes were detected in mammary epithelial MCF10A cells engineered to constitutively overexpress ectopic hepsin. The authenticity of the 31 kDa catalytically active form was verified by shRNA knockdown (Figures 1e and f).…”
Section: Resultsmentioning
confidence: 99%
“…10,12,13 Studies in hepsin knockout mice suggest the involvement of endogenous levels of hepsin in conversion of pro-HGF to HGF and MET receptor activation. 14 Hepsin also cleaves zymogens of other cell-surface serine proteases. Hepsin-mediated cleavage activates, for example, prostasin, a glycosylphosphatidylinositol-anchored serine protease.…”
Section: Introductionmentioning
confidence: 99%
“…It has been shown that hepsin is not an essential gene and knockout mice are viable and fertile [130, 131], although they do exhibit hearing loss due to developmental deformities in the cochlea [132], enlarged hepatocytes, and narrowed liver sinusoids [133]. Further, mice treated with the HepIn-13 inhibitor did not develop any apparent deficiencies [125], suggesting that targeting this TTSP would not cause any major detrimental side effects in humans, although more rigorous studies are needed.…”
Section: Ttsps As Novel Therapeutic Targets In Cancermentioning
confidence: 99%